Photoaffinity labeling of the porcine brain alpha 2-adrenergic receptor using a radioiodinated arylazide derivative of rauwolscine: identification of the hormone-binding subunit. - Lanier, S M (1986)
A functionalized derivative of the alpha 2-selective antagonist rauwolscine formed the basis for a photoaffinity adduct that has allowed identification of the hormone-binding subunit of the brain alpha 2-adrenergic receptor protein. Rauwolscine carboxylate underwent reaction with 4-N-t-butyloxycarbonyl-aminoaniline, leading to the synthesis of rauwolscine 4-aminophenyl carboxamide (Rau-AmPC). Rau-AmPC was radioiodinated and converted to the arylazide derivative, 17 alpha-hydroxy-20 alpha-yohimban-16 beta-[N-(4-azido-3-[125I]iodo)phenyl] carboxamide (125I-Rau-AzPC), via a diazonium salt intermediate. The characterization of 125I-Rau-AzPC as a photolabile probe employed alpha 2-adrenergic receptors, which were first solubilized from porcine brain membranes and partially purified by affinity chromatography utilizing a yohimbine-agarose affinity matrix. In the partially purified receptor preparation incubated with 125I-Rau-AzPC, photolysis resulted in covalent labeling of a major (Mr, 62,000) peptide as determined by NaDodSO4/PAGE and autoradiography. Labeling of this peptide was inhibited by the alpha 2-selective antagonist, yohimbine, and the non-subtype-selective alpha-antagonist, phentolamine, but not by the alpha 1-antagonist, prazosin, or the beta-receptor antagonist, (-)-alprenolol. The alpha-adrenergic agonist epinephrine also inhibited labeling in a stereoselective manner. These data indicate that the photolabeled Mr 62,000 peptide is the hormone-binding subunit of the alpha 2-adrenergic receptor protein. The availability of this radioiodinated photoaffinity probe for the alpha 2-adrenergic receptor should facilitate further structural and biophysical characterization of the receptor protein.